Line Spread Test Results for Commercially Available the White Rice Porridge with Egg - Including the Effect of Four types of Thickening Agents Added after Blending (Global Journal of Medical Research, 2023)
Viscosity was evaluated using a line spread test LST using white rice porridge with egg which has more lipids and proteins than white rice porridge and has a wide range of versatility Liquid porridge is used for older people with weak chewing and babies as baby food have low viscosity and are highly likely to be aspirated by people with weakened swallowing function Therefore a uniform liquid porridge was prepared using a mixer and the viscosity was measured As a result it was shown that liquid porridge is thin and has a high risk of aspiration in people with weakened swallowing function In order to increase the viscosity of the liquefied white rice porridge with egg commercially available thickeners four different types were added The viscosity of white rice porridge with egg with added thickener was evaluated using the line spread test LST
Keywords: commercial product; white rice porridge with egg; lin spread test (LST); thickener